Interactive Learning Media Arrange Animal Names Based on Android Game - Nur Khafidhoh; Ichwanda Ahmad Noviandy (LPPM Universitas KH. A. Wahab Hasbullah, 2022)
The game is one of the important factors in the growth of children. Utilization and use of educational games can support the learning process of children. With the educational games, it is hoped that children's enthusiasm for learning will be more motivated. Educational games can create a pleasant atmosphere in the child's learning process. The images, music and sounds that appear make the child not feel bored, because the nature of the child likes to be bored when learning to use the written form. The making of the game